Textual Silences and Literary Choices in al-Kisāʾī's Account of the Annunciation and the Birth of Jesus - Blatherwick, Helen (Arabica, 2019)
The story of the Annunciation to Mary and the birth of Jesus in the Qurʾān and the Bible has been the subject of several recent literary studies that bring up the use of textual silences, and the significance of speech and speechlessness as themes in the text. This paper focuses on three recensions of the story available to us in printed editions of al-Kisāʾī's Qiṣaṣ al-anbiyāʾ in similar vein, through intertextual comparison of these accounts with Mary stories as told in the Qurʾān, premodern qiṣaṣ collections, and Islamic historiographical sources. By comparing al-Kisāʾī's accounts of the Annunciation with those told in the Qurʾān and the wider Islamic Mary corpus it is possible to gain insight into the author's literary agenda, and also into the ways in which he draws on the wider narrative pool for his material, makes reference to the Qurʾān, and manipulates theme and characterisation.